Stem Cell-Derived Exosome Therapy for Dental Diseases: From Bench to Bed in Dentistry - Reham Al Jasser (Pakistan Journal of Medical & Health Sciences, 2022)
Stem cells are undifferentiated cells that have significant potential to regenerate missing tissues and living structures. Exosomes are a specific subgroup of extracellular vesicles that are recognized as important mediators of intercellular communication in the process of regeneration. They contribute to various pathways of physiological and pathological processes. Given the ability of exosomes to carry molecular cargos and transfer bioactive components, exosome-based disease diagnosis and therapeutics have been extensively studied over the past few decades. The present review highlights the emerging applications of exosomes as therapeutic agents in craniofacial and dental regenerative processes. In addition, the current challenges and future perspectives of exosomes in dental clinical applications are discussed.